2019
DOI: 10.1371/journal.pone.0219209
|View full text |Cite
|
Sign up to set email alerts
|

The leaf-air temperature difference reflects the variation in water status and photosynthesis of sorghum under waterlogged conditions

Abstract: Waterlogging stress is one of the most important abiotic stresses limiting sorghum growth and development. Consequently, the responses of sorghum to waterlogging must be monitored and studied. This study investigated changes in the leaf water status, xylem exudation rate, leaf anatomical structure, leaf temperature and photosynthetic performance. Waterlogging-tolerant (Jinuoliang 01, abbreviated JN01) and waterlogging-sensitive (Jinza 31, abbreviated JZ31) sorghum cultivars were planted in pots. The experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 32 publications
(28 reference statements)
2
30
1
Order By: Relevance
“…The water content of leaf is one of the major physiological indicators that reflects their ability to withstand adversity in stressful environments [78,79]. Heat and drought stress cause decreased water uptake and increased transpiration of plants, significantly impeding efficient water utilization and moisture retention of leaf [7,80].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The water content of leaf is one of the major physiological indicators that reflects their ability to withstand adversity in stressful environments [78,79]. Heat and drought stress cause decreased water uptake and increased transpiration of plants, significantly impeding efficient water utilization and moisture retention of leaf [7,80].…”
Section: Discussionmentioning
confidence: 99%
“…Heat and drought stress cause decreased water uptake and increased transpiration of plants, significantly impeding efficient water utilization and moisture retention of leaf [7,80]. It has been demonstrated that the leaf-air temperature difference of soybean plants measured through high-resolution thermal IR images under various moisture stresses correlated with the leaf water content [79]. We phenotyped plant temperature by FLIR thermography, and the results indicate that leaf temperature of OsERF115/AP2EREBP110-OE plants was lower than WT plants under the heat-drought combined stress conditions (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Such difference could be due to the low energy input in the controlled environment growth room, the crop being grown in a hydroponic setup, minimal heat waste from the light source (LED lights) and constant air circulation in the growth room. In previous studies, CTD values of 7.5, 10, and 12 • C have been reported for sorghum (Zhang et al, 2019), alfalfa (Moran et al, 1994) and soybean (Hou et al, 2019), respectively.…”
Section: Discussionmentioning
confidence: 85%
“…However, no changes were observed in the carotenoid pool, occurring a decrease in photochemical quenching and an increase in non-photochemical quenching (NPQ), leading to a decrease in the lumen pH, attributed to protonation of the light-harvesting complexes (LHC) proteins associated with the PSII (Cousins et al, 2002). This, in turn, can explain the increase in leaf temperature observed in the waterlogged plants (Zhang et al, 2019). Moreover, it was possible to observe that waterlogged plants had their trapped and transported energy fluxes reduced, but no increase in the energy dissipation.…”
Section: Discussionmentioning
confidence: 99%